EFFECT OF DIFFERENT ZONING ON CLOSED HOUSE SYSTEM ON CHEMICAL-PHYSICAL QUALITY OF BROILER MEAT - S. A. R., Sipahutar; Miwada, I N. S.; Ariana, I N. T. (Jurnal Peternakan Tropika, 2023)
Broiler is a type of poultry that has homeothermic properties, namely keeping its body temperature constant even though it is at an environmental temperature higher than its body temperature, so closed cages are used to minimize outside weather disturbances that may be experienced by livestock such as heat and rain.  The purpose of this study was to determine the effect of zoning in a closed house cage on the chemical-physical quality of broiler meat and determine the best zoning for rearing broiler chickens in a closed house cage. This study used Day Old Chick (DOC) broiler chickens as many as 20,000 which were kept until the 29th day in a closed house cage which was divided into four zones, namely Z1 (0 - 30 m from the inlet (front of the closed house cage)), or Z2 (30 - 60 m from the inlet (front of the closed house)), Z3 (60 - 90 m from the inlet (front of the closed house)), and Z4 (90 - 120 m from the inlet (front of the closed house) ). Observation of air temperature and humidity was carried out every 2 days at 09.00 WITA, 14.00 WITA, and 17.00 WITA from day 7 to day 29. On day 21, 16 chickens were randomly selected from each zone for research. the effect of zoning on the chemical-physical quality of broiler meat. The results showed that zoning had no significant effect (P>0.05) on the pH value, the pH value ranged from 6.20 to 6.29. The observed water content was not significantly different (P>0.05), which was in the range of 78.49% - 81.41%. The Cooking Loss observed was not significantly different (P>0.05) the Cooking Loss range was between 32.83% - 36.00%. The results of statistical analysis showed that the protein content was not significantly different (P>0.05) in the normal range between 20.89% - 21.63%. From the results of this study, it can be concluded that different zoning in the closed house system does not affect the chemical-physical quality of broiler meat.   Keywords: zoning, closed house, chemical-physics, broiler chicken meat